MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR TENTANG MENGENAL SIFAT-SIFAT ALLAH.SWT DENGAN PENERAPAN MODEL PENGAJARAN DISKUSI PADA SISWA KELAS IV-B DI SDN JENGGAWAH 01 KECAMATAN JENGGAWAH JEMBER SEMESTER I TAHUN PELAJARAN 2012/2013 - Husen Habawi (FKIP Universitas Islam Jember, 2014)
Based on the preliminary study conducted by the researcher, the fourth grade students at SDN Jenggawah 01 are lack of motivation so that it badly affects on their learning outcome. To copewith this problem, a teacher can use wide variety strategies to motivate his/her students to behigh-motivated person and advance their learning outcome. Discussion is one of strategies that can be used to deal with this. This study is therefore devoted to investigate of how discussion technique can be implemented to motivate them and advance their learning outcome.It is aimed at the main purpose:how to develop and implement practical and effective model of teaching and learning to the sixth graders in SDN Jenggawah 01 with discussion technique to increase their motivation andand advance their learning outcome of introducing the attributes of Allah. The classroom action research was chosen as the research design in this study. It was undertaken two cycles. Each cycle consists of four stages namely planning, implementing/acting, observing, and revising/reflecting. The subject of this research is the students of class IV B of SDN Jenggawah 01, in academic year 2012/2013. The data are collected in the form of qualitative and quantitative. Qualitative data are obtained from observation during the teaching-learning process about the whole activities and students’ behavior. The latter are obtained from the test. The findings of the research show that discussion can be used as an effective model of teaching and learning having positive effects in increasing students’ motivation and to advance their learning outcome. This can be shown from by the increase of criteria of the action success, from 68,4% (cycle 1) to 100% (cycle 2).Keywords: Motivation, Learning outcome, Islamic education, Discussion technique.